Crystal structure of (2-([1,1-bis(hydroxymethyl)-2-oxyethyl]iminomethyl)-5-(n-decyl)phenolato)-dimethyl-tin(IV), C23H39NO5Sn - Lee See Mun; Lo Kong Mun; Tiekink Edward R.T. (Zeitschrift für Kristallographie - New Crystal Structures, 2019)
C23H39NO5Sn, triclinic, P1̄ (no. 2), a = 6.0101(2) Å, b = 9.2999(2) Å, c = 22.3110(6) Å, α = 91.482(2)°, β = 90.594(3)°, γ = 102.631(2)°, V = 1216.28(6) Å3, Z = 2, Rgt(F) = 0.0425, wRref(F2) = 0.1158, T = 100(2) K.